La comprensión auditiva de la entonación irónica en alumnos de ELE brasileños con un nivel C1 - Berrio, Sara González [UNESP]; Leralta, Susana Martín (My University, 2015)
Our main objective with this research was to analyse the comprehension of ironic intonation by Brazilian students with a C1 level in Spanish as a Second Language. Furthermore, we studied the importance of intonation and context knowledge when elaborating ironic meanings. In order to achieve those goals we developed a focused description with 40 participants: 20 native speakers and 20 non-native speakers. Both groups conducted two comprehension tests - one decontextualized and another one contextualized-. The data gathered shows that it is difficult for Brazilian students to identify irony just through intonation. Besides, it reveals that, contrary to what happens with native speakers, they give more importance to the context than intonation when elaborating ironic meanings. All in all, the preset paper underlines the lack of phono-pragmatic resources by the Brazilian students that took part in our inquiry.
The comprehension of ironic intonation by brazilian students with a C1 level in Spanish as a second language
Keywords: C1 brazilian students; Intonation; Irony; Phono-pragmatics; Spanish as a Second Language